State of the Art: trxG Factor Regulation of Post-embryonic Plant Development - Fletcher, Jennifer C. (Frontiers in Plant Science, 2017)
Multicellular organisms rely on the precise and consistent regulation of gene expression to direct their development in tissue- and cell-type specific patterns. This regulatory activity involves arrays of DNA-binding transcription factors and epigenetic factors that modify chromatin structure. Among the chromatin modifiers, trithorax (trxG) and Polycomb (PcG) group proteins play important roles in orchestrating the stable activation and repression of gene expression, respectively. These proteins have generally antagonistic functions in maintaining cell and tissue homeostasis as well as in mediating widespread transcriptional reprogramming during developmental transitions. Plants utilize multiple trxG factors to regulate gene transcription as they modulate their development in response to both endogenous and environmental cues. Here I will discuss the roles of trxG factors and their associated proteins in post-embryonic plant development.